Woody Species Composition and Diversity of Wawa-Zange Forest, Gombe State, Nigeria (Asian Journal of Plant Biology, 2022)
According to recent research, severe human-induced deforestation is causing 65 percent of the thirty Forest Reserves spread over Gombe State to progressively transform into the desert. The research was done in the Wawa-Zange Forest Reserve in Gombe State, Nigeria, to assess the richness of woody species and biodiversity preservation. The vegetation was sampled with the Point Centered Quarter technique. A complete enumeration of Woody (Trees and Shrubs) with (Diameter at Breast Height or DBH) ≥10 and ≥5cm was carried out. Using Simpson's Diversity and the Shannon-Wiener index, alpha diversity was evaluated. A total of 51 woody species from 16 families and 41 genera were discovered. 34 were trees while 17 were shrubs. Most species were found in the Fabaceae family. Ceasalpinoidae (10), Mimosoideae (4), Papilionoideae (3), Combretaceae (7), Rubiaceae (5), Anacardiaceae, Burseraceae, Capparaceae , Moraceae, Tiliaceae had two species each. The other families are namely Apocynaceae, Ebanaceae, Loganiaceae, Meliaceae, Rhamnaceae, Sapotaceae, Zygophyllaceae with one species each. Simpson index of Diversity was (0.55) and the Shannon-Wiener index was (2.07). This study concluded that plants with low Importance Value Index or IVI such as Pterocarpus erinaceous, Capparis mitchelli, and Pericopsis laxiflora need urgent conservation measures. Therefore, it is important to properly adopt conservation and sustainable management measures.
Keywords: Woody Species; Biodiversity; Conservation; Wawa-Zange; Forest-Reserve